Hybrid Active-Passive Space Radiation Simulation Concept for GSI and the Future FAIR Facility - Schuy, Christoph; Weber, Uli; Durante, Marco (Frontiers in Physics, 2020)
Space radiation is acknowledged as one of the main health risks for human exploration of the Solar system. Solar particle events (SPE) and the galactic cosmic radiation (GCR) can cause significant early and late morbidity, and damage mission critical microelectronics. Systematic studies of the interaction of energetic heavy ions with biological and electronic systems are typically performed at high-energy particle accelerators with a small subset of ions and energies in an independent and serialized way. This simplification can lead to inaccurate estimations of the harmful radiation effects of the full space radiation environment on man and machine. To mitigate these limitations, NASA has developed an irradiation system at the Brookhaven National Laboratory able to simulate the full GCR spectrum. ESA is also investing in ground-based space radiation studies in Europe, using the current and future facilities at GSI/FAIR in Darmstadt (Germany). We describe here an advanced hybrid active-passive space radiation simulation system to simulate GCR or SPE spectra. A predefined set of different monoenergetic 56Fe beams will be fired on specially designed beam modulators consisting of filigree periodic structures. Their thickness, composition and geometry per used primary beam energy are optimized via 1D-transport calculations in such a way that the superposition of the produced radiation fields at the target position closely simulate the GCR in different scenarios. The highly complex modulators will be built using state-of-the-art manufacturing techniques like 3D-printing and precision casting. A Monte Carlo simulation of the spectrum produced in this setup is reported.